RBCK1‐related disease: A rare multisystem disorder with polyglucosan storage, auto‐inflammation, recurrent infections, skeletal, and cardiac myopathy—Four additional patients and a review of the current literature. Issue 5 (16th April 2020) - Phadke, Rahul; Hedberg‐Oldfors, Carola; Scalco, Renata S.; Lowe, David M.; Ashworth, Michael; Novelli, Marco; Vara, Roshni; Merwick, Aine; Amer, Halima; Sofat, Reecha; Sugarman, Max; Jovanovic, Ana; et al.
Abstract: In this article, we report four new patients, from three kindreds, with pathogenic variants in RBCK1 and a multisystem disorder characterised by widespread polyglucosan storage. We describe the clinical presentation of progressive skeletal and cardiac myopathy, combined immunodeficiencies and auto‐inflammation, illustrate in detail the histopathological findings in multiple tissue types, and report muscle MRI findings.